Moda e processos de criação: ações comunicacionais a partir da montagem de looks - Panisson, Luciane Salete (2012)
This research approaches the building of an outfit as an individual creative process, which happens in a cultural environment that allows the consumer to become the author by matching products through their use. These different kinds of behavior are gaining strengths and influencing designers to rethink their creations, in favor of esthetics proposed by their users, fact that deserves deeper studies about its creation procedures. For this matter, the comprehension of the individual creational process inside culture occurs from the following questioning: How can the creative process of individuals be identified in the composition of their outfit from the perusal of their usage? What are the differences between the spectacle created by internet users and what actually is seen in the streets? The elucidation of this questioning aims to identify the composition procedures of an outfit as a process of creation in culture and, from this identification, discuss how the change in the communicative flow of who produces and who receives visual messages occurs. As specific objectives, this paper searches for the detection of creative resources which people use in the composition of their outfit and the development of a visual reading system that may assist this observation, elaborated from the concept of Networking Creation. The theoretical contribution which leads this study begins in the contextualization of fashion and style as social processes that allow the self-narratives (BARNARD, 2006; CRANE 2008; MIRANDA, 2008; ROCHE, 2007, SVENDSEN, 2010, MESQUITA, 2008), by cultural theoreticians who approach the changes in the roles of individuals from users to creators of visual messages through the use of products (CERTEAU, 1994 e LURIE, 1997), their transformation in intercultural beings (CANCLINI, 2003) inserted into the culture, but distinguished from it (COLAPIETRO, 1989) and that become creators (MORACE, 2009), finalizing with theories of Net Creation (SALLES, 2008) and Post-Production (BOURRIAUD, 2009) which will serve as base for the comprehension of the outfit composition as a creative process. Starting with images of this users-creators day by day in the streets and comparing them to images posted in the web by the users themselves, from 2010 to 2012, procedures of outfit construction that allow the intersection of creative resources used by distinguishes individuals and that, up a new and innovative creative process, reveal post-production strategies of the outfit and the image